2022
DOI: 10.1111/poms.13733
|View full text |Cite
|
Sign up to set email alerts
|

Market positioning in food industry in response to public health policies

Abstract: Public health agencies have designed and implemented interventions to control the global obesity epidemic using healthfulness messaging and policy changes such as taxation. These changes in the policy environment and marketplace dynamics have shifted consumer trends and have challenged food producers in the industry. The following questions are considered in the food industry in such a context: (i) Should firms offer similar or very different quality offerings? (ii) How should a firm's positioning strategies c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…They proposed that aligning the network structure by focusing on the upstream-centric goods flow can decrease vulnerability to quality problems. Sajeesh et al (2022) used a duopolistic competition model to explore how customers' awareness of health and taxation change influence firms' quality decisions. They showed that greater awareness of health and taxation could enlarge and reduce the quality gap between alternatives, respectively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They proposed that aligning the network structure by focusing on the upstream-centric goods flow can decrease vulnerability to quality problems. Sajeesh et al (2022) used a duopolistic competition model to explore how customers' awareness of health and taxation change influence firms' quality decisions. They showed that greater awareness of health and taxation could enlarge and reduce the quality gap between alternatives, respectively.…”
Section: Literature Reviewmentioning
confidence: 99%